A study on assessment of inappropriate prescribing of proton pump inhibitors at a teaching hospital - Patil, Neelkantreddy; Biyabani, Syed Afzal Uddin; Naema, Hafsa; Neelur, Basavaraj; Biradar, Prashant; Kulkarni, Anirudh (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Proton pump inhibitors (PPI’s) are amongst the most extensively utilized therapies for conditions characterized by excessive gastric-acid production, making them highly susceptible to inappropriate long-term use predisposing individuals to a higher risk of side effects. This study seeks to evaluate the prevalence and patterns of inappropriate PPI prescribing in both in-patients and out-patients, with a focus on adherence to clinical guidelines regarding indications, dosage, frequency, and duration of therapy by using National Institute for Health and Care Excellence (NICE) guidelines. Methods: Appropriateness of PPI prescriptions was prospectively assessed in 120 in-patients during their hospitalization and at discharge, and 50 out-patients with regard to the indication, dosage, frequency and duration of therapy for their compliance with NICE guidelines. The required data for the study was noted in a suitably designed data collection form. Results: Among 120 in-patients, 56 (46.67%) were males and 64 (53.33%) were females. Pantoprazole 40 mg was the commonly prescribed PPI, accounting 115 (95.83%) IV and 5 (4.17%) oral prescriptions among In-patients whereas 94 (93.07%) prescriptions account for pantoprazole 40 mg and 7 (6.93%) with rabeprazole 20 mg during discharge, all through an oral route. On assessing the appropriateness of prescription, it was revealed that 80 (66.67%) were appropriate, while 40 (33.33%) were inappropriate in IPD. In 35 inappropriate indications, 14 (40%) are due to prophylaxis in low-risk patients with concomitant use of NSAIDs and 1 (2.86%) with corticosteroids. Twenty (57.15%) prescriptions had no indications. Four (10%) prescriptions had inappropriate frequency and 1 (2.50%) had inappropriate duration. Among the out-patients, 32 (64%) were males and 18 (36%) females. Pantoprazole 40 mg was prescribed in 5 (10%) through an IV route and 32 (64%) were oral prescriptions whereas 13 (26%) were given rabeprazole 20 mg orally. Inappropriateness was seen in 14 (77.78%) due to prophylaxis in low-risk patients co-prescribed with NSAIDs and 4 (22.22%) prescriptions had no clear indications. Three (14.29%) accounted for inappropriate frequency. Conclusions: The study concludes that, the rate of inappropriate prescribing of PPIs is relatively low in both in-patients during hospitalization, at discharge, and in outpatients. Pharmacists can work closely with prescribers to ensure the proper indication, dose, frequency and duration of therapy.